Internal migration in a developing country: A panel data analysis of Ecuador (1982-2010) - Ordoñez Cuenca, J. (2016)
In this study, we adopt a random utility maximization (RUM) theoretical model, based on differences in economic expectations between the provinces of origin and destination. We use census data from 1974 to 2010 to propose and estimate a model of interregional migration, considering various key factors: population, distance, production structure, and urbaniszation. We also controll for factors that affect the selectivity of migration, such as age structure or level of education